UPAYA PENINGKATAN DISIPLIN KERJA KARYAWAN DALAM MENINGKATKAN KINERJA KARYAWAN PADA KELURAHAN BANGUNTAPAN - Suhartono; Subekti, Eko Surachmi; Nugroho, Muhammad Awal Satrio (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2024)
The role of work discipline is crucial in enhancing employee performance, as a higher level of discipline directly impacts responsibility and work quality. This study aims to identify the factors contributing to the decline in work discipline at the Banguntapan sub-district office and to formulate improvement efforts. The research sample consisted of five employees, including the Head of Affairs and the Head of Section, who supervise staff. Data were collected through observation and interviews. Data analysis was conducted using Miles and Huberman’s interactive analysis model, which includes data collection, reduction, presentation, and conclusion drawing. The result indicated that the factors causing the decline in work discipline at the Banguntapan sub-district office included punctuality, compliance with regulations, and responsibility for tasks. This study offers recommendations for improving word discipline, such as providing varied recognition, standardizing right and obligations, and enhancing facilities.